Pengaruh Citra Merek Terhadap Daya Beli Konsumen Pada CW Coffee di Kota Pontianak - Rendy Amy Saputra (IJAcc, 2022)
This study aims to investigate the impact of brand image on the purchasing power of CW Coffee consumers in Pontianak. The respondents in this study were customers who visited CW Coffee in Pontianak. The tools in this study are data quality tests, which include validity tests, reliability tests, simple regression analysis, and hypothesis tests (t-tests). This study shows that brand image has a positive and significant impact on purchasing power